Communicating with clarity - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
editing and publication workshop from February 13-24 1989. The work shop was organized in conjunction with the IITA, who hosted it at their headquarters in Ibadan, Nigeria